2018
DOI: 10.1111/jace.15422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and color properties of the TiO2@CoAl2O4 blue pigments with low cobalt content applied in ceramic glaze

Abstract: The TiO2@CoAl2O4 complex blue pigments with low cobalt content were synthesized through calcinations of the precursor obtained from coprecipitating Co2+ and Al3+ to form Co‐Al LDHs (layered double hydroxides) on the surface of TiO2 particles. The structure and the properties of the synthesized pigments were characterized by XRD, SEM, TEM, UV‐Vis spectroscopy, XPS, and colorimeter. The precursors of the blue TiO2@CoAl2O4 complex pigments were consisted of LDHs shell layer encapsulated TiO2 microsphere. After ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In contrast, an increase in the proportion of cobalt aluminate caused an increase in C * because cobalt aluminate has an intense blue color. In addition, the cobalt blue color is attributed to 4 A 2 (F)→ 4 T 1 (P) of the d–d transition of the tetrahedrally coordinated Co 2+ ion . The band gap of the synthesized cobalt blue becomes uniform and the absorption wavelength becomes constant with increasing crystalline size, and C * increases.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, an increase in the proportion of cobalt aluminate caused an increase in C * because cobalt aluminate has an intense blue color. In addition, the cobalt blue color is attributed to 4 A 2 (F)→ 4 T 1 (P) of the d–d transition of the tetrahedrally coordinated Co 2+ ion . The band gap of the synthesized cobalt blue becomes uniform and the absorption wavelength becomes constant with increasing crystalline size, and C * increases.…”
Section: Resultsmentioning
confidence: 93%
“…However, cobalt is scarce and expensive, therefore the production costs of cobalt‐based ceramic pigments are high. In addition, the manufacture of cobalt‐based ceramic pigments can cause serious environmental problems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with other metals, a softer pearly effect can be produced. Other alternative techniques may generate effects in ceramics that resemble iridescence and pearling, such as the use of titanium and cobalt (TiO 2 @CoAl 2 O 4 ) [41] for bright colours [42], zirconium pigments encapsulated with deep black colours [43], or zinc oxide-based iridescent metallic effect surfaces (ZnO) [44]. Some recent research has shown iridescent and pearl effects based on enamels containing zinc oxide, zirconium oxide, itrio oxide, titanium oxide, hafnium oxide and cerium oxide [45].…”
Section: Iridescent and Pearl Techniquesmentioning
confidence: 99%
“…However, merely blending inorganic particles to polymer matrix could not meet all the requirements. [ 15–17 ] Therefore, the new designing of microstructure of nanocomposites, containing the construction of multilayer and the arrangement of nanofillers, has been attracting much attention by researchers. [ 18–20 ] The electrical and mechanical properties of composites can be greatly improved by changing the dimension of nanofillers and making them have a certain orientation in polymer matrix.…”
Section: Introductionmentioning
confidence: 99%